PENGELOLA SAMPAH PESISIR ANORGANIK DAN ORGANIK DI KELURAHAN WATTANG SOREANG KECAMATAN SOREANG KOTA PAREPARE - Asmidar asmidar; Muhammad Saenong; hamsiah hamsiah; damis damis (Universitas Muhammadiyah Sidenreng Rappang, 2025)
The Community Service Program (PKM) in Wattang Soreang Village, Parepare City, was implemented to address coastal pollution caused by the accumulation of household waste, market waste, and fishing activities. The main objective of this activity was to increase community awareness, skills, and independence in managing waste through a participatory, collaborative, and educational approach. The methods included socialization, counseling, sorting training, the use of shredding machines, and the production of compost and liquid fertilizer through modified fermentation tanks. The results of the activity showed an increase in community capacity, as evidenced by the ability to sort waste, the active involvement of partners, and the production of community-based environmentally friendly processed products.